Build Your Own Chatbot for Any Music Course – It’s Easier Than You Think! - Art Brownlow (Journal of the Association for Technology in Music Instruction, 2026)
Imagine a teaching assistant available 24/7 to answer students’ questions and support their learning—now, with custom GPT chatbots, that vision is a reality. This session demonstrates two AI tools created for music history courses: an Informational Chatbot for course policies, assignments and deadlines; and a Tutor Chatbot for mastering course content. These tools enhance learning, accommodate diverse schedules, and improve efficiency by automating routine tasks. Attendees will learn to create their own custom AI chatbots while exploring practical insights and best practices, inspiring them to integrate AI into their classrooms.